American Water Willow Mediates Survival and Antipredator Behavior of Juvenile Largemouth Bass. Issue 5 (30th July 2015) - Stahr, Kristopher J.; Shoup, Daniel E.
Abstract: State and federal agencies typically introduce aquatic vegetation to increase the recruitment of sport fishes, particularly Largemouth Bass Micropterus salmoides . However, due to frequent turbidity and water‐level fluctuations, managers in the southern United States are often left to introduce emergent macrophytes instead of submersed macrophytes. Emergent macrophytes have less underwater structural complexity than most submersed macrophytes and therefore may not be as effective in reducing the predation risk of Largemouth Bass. Therefore, the objective of this study was to determine if American water willow Justicia americana, a common emergent macrophyte species introduced in reservoirs, increases the survival of juvenile Largemouth Bass when exposed to predation. Predator–prey interactions between 10 juvenile and 1 adult Largemouth Bass were observed in tanks with natural densities of American water willow and compared with similar trials in vegetation‐free control tanks. Each adult Largemouth Bass was tested once in each treatment (vegetation present or absent). Water willow significantly reduced the capture‐to‐attack ratio of adult Largemouth Bass and decreased the amount of time spent searching and the number of captures, resulting in significantly higher juvenile survival in the vegetated trials. Although water willow provided a similar increase in survival compared with previous studies using submersed macrophytes, the mechanism underlying this change differed, likely resulting from the more rigid stem design of water willow. We conclude water willow is an excellent candidate for establishment in reservoirs because it is easier to establish than many other macrophyte species yet still reduces predation risk on juvenile Largemouth Bass.